Expression of PD-L1, AR, and P53 in urothelial carcinoma and their correlation with clinical prognosis - ZHOU Xiaodie, Qi Rongxin, WANG Xuan, YU Bo, WANG Jianjun, SHI Qunli, RAO Qiu, BAO Wei (Zhenduanxue lilun yu shijian)
Objective This study aims to observe the expression of programmed cell death 1 ligand 1 (PD-L1), P53, and androgen receptor (AR) in tumor tissues of patients with urothelial carcinoma (UC) and analyze their correlation with patient prognosis. Methods A retrospective analysis was conducted on 115 UC patients with complete clinical data who were admitted consecutively to the General Hospital of Eastern Theater Command and Nanjing Drum Tower Hospital from May 2017 to February 2020. Immunohistochemistry was used to detect the expression of PD-L1, P53, and AR proteins in pathological tissues. The chi-square test (χ² test) was employed to analyze the correlation between these biomarkers and clinicopathological characteristics. Kaplan-Meier survival analysis was used to evaluate the relationship between biomarker expression and prognosis. Results The median follow-up time for the study cohort was 32.5 months (range: 1-54 months). Disease progression occurred in 22 cases, and 17 patients (17.2%) died. The expression rates of PD-L1, P53, and AR in UC tissues were 46.1%, 45.2%, and 7.8%, respectively. Positive PD-L1 expression was associated with clinical progression (54.9% in the positive group vs. 31.8% in the negative group, P=0.016). AR-positive cases were more likely to exhibit multifocal tumor growth (21.7% vs. 4.3%, P=0.019). P53 expression showed no significant correlation with the clinical characteristics of UC. The positive expression of PD-L1, P53, and AR was not associated with overall survival in UC patients. Conclusion Positive PD-L1 expression is associated with disease progression in UC. The expression of PD-L1, P53, and AR is not correlated with short-term survival prognosis in UC patients. Among them, AR expression rate is low and shows no association with short-term prognosis, suggesting that AR-targeted therapy for UC patients has certain limitations.